2017
DOI: 10.5603/kp.a2017.0058
|View full text |Cite
|
Sign up to set email alerts
|

The effect of radiofrequency catheter ablation of frequent premature ventricular complexes and arrhythmia burden on left ventricular function

Abstract: A b s t r a c tBackground: Frequent premature ventricular complexes (PVC) are related to reversible tachycardia-induced cardiomyopathy. However, the role of arrhythmia burden on the outcome of the catheter ablation has not been fully recognised. Aim:The aim of this study was to assess the effect of catheter ablation and PVC burden in patients with and without structural heart disease (SHD) on left ventricular ejection fraction (LVEF). Methods:Transthoracic echocardiography was done before and six months after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Very few studies have reported relevant data where cut off values of 13%, or >20000/24 h predicted >5% increase in LVEF after RF ablation. This finding was consistent among patients with resting normal EF or those with LV dysfunction in absence or presence of SHD like in the current study 17, 18…”
Section: Discussionsupporting
confidence: 91%
“…Very few studies have reported relevant data where cut off values of 13%, or >20000/24 h predicted >5% increase in LVEF after RF ablation. This finding was consistent among patients with resting normal EF or those with LV dysfunction in absence or presence of SHD like in the current study 17, 18…”
Section: Discussionsupporting
confidence: 91%
“…The efficacy of RFCA in the management of LV systolic function was questioned in several trials, and a favorable effect of this modality on LV as well as RV systolic function was demonstrated [3,20]. Two important meta-analyses were conducted on these trials.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies confirm the relation between PVC burden (10%-20%) and the rate of LVEF positive reversal. [16][17][18][19] In patients with successful RFCA therapy, even a 14% increase in LVEF and a 5-mm mean decrease of LVEDd was observed. In patients with preexisting LV dysfunction, the improvement was not as great.…”
Section: Conflict Of Interest None Declaredmentioning
confidence: 98%
“…On the other hand, reduction in LVEDd was significant in the OT group: from 54 (9) to 51 (12) (P = 0.015). Patients in the OT group had an increased ejection fraction after ablation than before (52% [12] vs 58% [13]; P <0.001) in comparison with the VENT group (47% [16] vs 50% [15]; P = 0.08; FIGURE 3), despite higher baseline LVEF values before the procedure in the OT group than the VENT group (mean [SD], 52 [12] vs 47 [16]; P = 0.001).…”
Section: Left Ventricular Function Improvementmentioning
confidence: 98%
See 1 more Smart Citation